Comparison of Molecular International Prognostic Scoring System (M-IPSS) and Revised International Prognostic Scoring System (R-IPSS) in Thai patients with myelodysplastic neoplasms - Polprasert C. (2023)
Introduction: Risk stratification is essential for treatment decision in myelodysplastic neoplasms (MDS). Molecular international prognostic scoring system (M-IPSS) has been recently developed combining somatic mutations and clinical information being used in the revised international prognostic scoring system (R-IPSS). Objective: We aimed to explore the performances of M-IPSS and R-IPSS in Thai patients with MDS. Method: MDS patients were stratified into risk categories using R-IPSS and M-IPSS scores. The performance of both models were evaluated for prognostic prediction. Results: One hundred and sixty-two MDS patients were recruited from the multicenter study. Survival analysis revealed that both R-IPSS and M-IPSS were good prediction models with the Concordance Index (C-index) of 0.71 (95% Confidence interval [CI] 0.64–0.78) and 0.75 (95% CI 0.69–0.80), respectively (p = 0.22). Comparing the two, 13 of 162 (8%) cases were re-staged between lower and higher risks which would have affected treatment decisions. Conclusion: Our study showed that R-IPSS score can be used for risk stratification in most Thai patients. A prediction model using somatic mutations specifically in Asian patients should be formulated in the future.